1977
DOI: 10.1007/bf00745135
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin: A diabetogenic hormone

Abstract: Summary. During an oral glucose tolerance test (OGTT) glucose and insulin levels were measured in 26 patients with prolactin-producing pituitary tumours without growth hormone excess. Basal glucose and insulin levels did not differ from the values of an age-matched control group. After glucose load the hyperprolactinaemic patients showed a decrease in glucose tolerance and a hyperinsulinaemia. Bromocriptine (CB 154), which suppressed PRL, improved glucose tolerance and decreased insulin towards normal in a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
89
2
5

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(104 citation statements)
references
References 17 publications
8
89
2
5
Order By: Relevance
“…circulating levels as in patients with pituitary adenomas [1,2]. We found normal basal prolactin concentrations and normal prolactin responses to TRH in patients with severe diabetic ketoacidosis, suggesting no important role for prolactin in this condition.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…circulating levels as in patients with pituitary adenomas [1,2]. We found normal basal prolactin concentrations and normal prolactin responses to TRH in patients with severe diabetic ketoacidosis, suggesting no important role for prolactin in this condition.…”
Section: Discussionsupporting
confidence: 46%
“…There was no correlation between basal prolactin concentrations, or magnitude of prolactin responses to TRH, and any of the metabolic variables measured. These findings do not suggest a role for prolactin in the development of diabetic ketoacidosis.Key words: Prolactin, diabetic ketoacidosis, plasma sodium, plasma osmolality, TRH test.Prolactin is said to have diabetogenic properties [1,2] and, in several animal species, plays a role in sodium and water retention [3]. Elevated prolactin concentrations have been reported in diabetic ketoacidosis and it was suggested that prolactin might participate in sodium retention in this condition [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since PRL has been considered to be a diabetogenic hormone (Landgraf et al 1977), we thought it of interest to explore PRL secretion in children with newly diagnosed IDD. The previous reports on basal PRL release and the response to provocative stimuli in patients with IDD have been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was reported that the administration of prolactin (PRL) elicited hyperglycemia (Rathgeb et al 1971) and that an impaired glucose tolerance and hyperinsulinemia were observed after glucose load in patients with hyperprolactinemia (Landgraf et al 1977), PRL has been considered to exert a diabetogenic action. It, therefore, seems to be of interest to explore PRL release in diabetes mellitus.…”
mentioning
confidence: 99%